The analysis of pedaling techniques with platform pedals - Stępniewski, Andrzej A.; Grudziński, Jerzy (Zielona Góra: Uniwersytet Zielonogórski)
The paper analyzes a pedaling technique with platform pedals in which the influence of the geometric and tribological parameters on the torque course of the active forces in the crank rotation axis is determined. Distribution of forces of feet acting on pedals as a function of the crank rotation angle was performed and on this basis the specific pedaling zones and their ranges and the courses of the value of variable active torque and pedaling work during the full cycle were determined. The course of changes in the movements in the ankle joint is described with a function depending on the crank and limb position and loading of the joint. A numerical example has also been presented and a discussion of the results has been carried out.
Keywords: cycling; platform-pedal; pedaling; cycling efficiency